Diversidade genética, frequência de irrigação e doses de polímero hidrorretentor na produção de goiabeira - Pereira, Eduardo Castro (2017)
The use of water-repellent polymer in agriculture has been growing in recent years because it has the capacity to retain and provide water slowly to the plants and still be a conditioner for soils. However, the lack of studies for the guava crop and its ideal dose for use in substrates makes its use limited in this context. Another important aspect of guava culture is the study of diversity, which is one of the most important indicators evaluated by plant breeders in the initial phase of a breeding program. The aim of this work was to evaluate the effects of different hydrogel doses and irrigation shifts on the growth of guinea - pig grafts and to evaluate the diversity of guava accesses using morphoagronomic descriptors for qualitative variables in the plant and qualitative and quantitative variables in the fruits. In the experiment I, the experimental design was a randomized block design, with four replications, in the 4 x 3 factorial scheme, corresponding to four doses of the Biogel Aqua Plus® hydrogelent polymer (0.0, 1.0, 2.5 e 5.0 g L-1) and three irrigation shifts (T1 - daily irrigation; T2 - irrigation on alternate days and T3 - irrigation every two days). The following variables were evaluated: height of the portagrafts (cm); Lap diameter (mm); Number of leaves per plant; Dry shoot mass (g), root dry mass weight (g) and total dry weight weight (g); Height / diameter ratio of the neck; Dry height / dry matter ratio; Dry mass ratio of aerial part / root dry mass and content index of chlorophyll. The 1g L-1 dose of the hydrogel incorporated into the substrate is indicated for the production of guinea-pig portagrafts and with the incorporation thereof, irrigation of the guinea-pig portagrafts can be performed frequently within one day. In the experiment II, the morphoagronomic descriptors were evaluated in 84 accessions of seminiferous guava trees cultivated at the experimental farm of UFERSA (Alagoinha), in the region of Mossoró-RN. We evaluated 26 descriptors in the plant, observed in four quadrants. The evaluation through morphoagronomic descriptors showed a partial agreement between the clusters methods studied. The technique of genetic dissimilarity using multicastropic characteristics was effective to investigate the diversity among the accessions of guava trees, showing that the population has wide genetic variability. The evaluation through morphoagronomic descriptors showed a partial agreement between the clusters methods studied. The technique of genetic dissimilarity using multicastropic characteristics was effective to investigate the diversity among the accessions of guava trees, showing that the population has wide genetic variability. In the experiment III, the quality and the morphoagronomic characteristics of fruits of 37 guinea-fowl accesses propagated semen, cultivated in the experimental farm of Ufersa (Alagoinha), in the region of Mossoró-RN, were evaluated. Five fruits were collected from each access and transported to the UFERSA post-harvest laboratory at the CPVSA. For the quality variables, 11 parameters were evaluated. Morphological variables were analyzed according to 13 descriptors. The Tocher optimization clustering methods and the UPGMA method demonstrated wide divergence in the division of groups into the quantitative characteristics. In the grouping carried out for the qualitative variables, the Tocher and UPGMA methods observed great variability among the accessions. The fruit length, fruit weight, firmness, septal shape, fruit shape and color of the epidermis were the main contributors to dissimilarity among the accessions